1998
DOI: 10.1046/j.1365-2044.1998.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

The theoretical ideal fresh‐gas flow sequence at the start of low‐flow anaesthesia

Abstract: SummaryA spreadsheet model of a circle breathing system and a 70-kg anaesthetised 'standard man' has been used to simulate the first 20 min of low-flow anaesthesia with halothane, enflurane, isoflurane, sevoflurane and desflurane in oxygen. It is shown that, with the fresh-gas flow set initially equal to the total ventilation and the fresh-gas partial pressure to 3 MAC, the end-expired partial pressure can be raised to 1 MAC in 1 min with desflurane and sevoflurane, 1.5 min with isoflurane, 2.5 min with enflur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 25 publications
3
40
0
1
Order By: Relevance
“…The computer simulation indicated that if the initial vaporiser setting is high (3 MAC) and if the target is an end-expired partial pressure of 1 MAC, the fresh gas flow can be reduced to low levels within 1±2 min for the three least soluble anaesthetic agents, isoflurane, sevoflurane and desflurane [1]. In general, the results of our clinical study support this (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The computer simulation indicated that if the initial vaporiser setting is high (3 MAC) and if the target is an end-expired partial pressure of 1 MAC, the fresh gas flow can be reduced to low levels within 1±2 min for the three least soluble anaesthetic agents, isoflurane, sevoflurane and desflurane [1]. In general, the results of our clinical study support this (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…2). It would be interesting to explore the reasons for these two observations, perhaps with the help of the Mapleson spreadsheet program [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is commonplace to observe the employment of higher than necessary fresh gas flows via semi-closed circle breathing systems despite the availability of validated, pragmatic, optimal initial flow and vaporiser setting regimens [1,2]. This results in widespread cost inefficiencies, excessive environmental pollution and poor breathing circuit conditioning [3].…”
mentioning
confidence: 99%